2008
DOI: 10.1007/s12298-008-0033-z
|View full text |Cite|
|
Sign up to set email alerts
|

TDZ-induced direct shoot organogenesis and somatic embryogenesis on cotyledonary node explants of lentil (Lens culinaris Medik.)

Abstract: An efficient and simple procedure for inducing high frequency direct shoot organogenesis and somatic embryogenesis in lentil from cotyledonary node explants (without both the cotyledons) in response to TDZ alone is reported. TDZ at concentration lower than 2.0 μM induced shoot organogenesis whereas at higher concentration (2.5-15 μM) it caused a shift in regeneration from shoot organogenesis to somatic embryogenesis. The cotyledonary node and seedling cultures developed only shoots even at high concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Commonly, embryogenesis is induced after inoculating the ideal scalps onto medium containing 2,4-D or other auxins (Schoofs et al, 1998;Sadik et al, 2007;Ramírez-Villalobos & De García, 2008). The formation of embryogenic callus under TDZ and 4-CPPU treatments as described in this study conforms to reports that at high concentrations, these urea-type cytokinins exhibit an auxin activity and thus could induce embryogenesis (Vinayak et al, 2009). Chhabra et al (2008 suggested that at high concentrations, TDZ imposes stress on the explant and could redirect its development from shoot organogenesis to somatic embryogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Commonly, embryogenesis is induced after inoculating the ideal scalps onto medium containing 2,4-D or other auxins (Schoofs et al, 1998;Sadik et al, 2007;Ramírez-Villalobos & De García, 2008). The formation of embryogenic callus under TDZ and 4-CPPU treatments as described in this study conforms to reports that at high concentrations, these urea-type cytokinins exhibit an auxin activity and thus could induce embryogenesis (Vinayak et al, 2009). Chhabra et al (2008 suggested that at high concentrations, TDZ imposes stress on the explant and could redirect its development from shoot organogenesis to somatic embryogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…Chhabra et al (2008 suggested that at high concentrations, TDZ imposes stress on the explant and could redirect its development from shoot organogenesis to somatic embryogenesis. At concentrations higher than 2 μM, TDZ induced direct somatic embryogenesis on cotyledonary node explants of recalcitrant lentil (Chhabra et al, 2008). Earlier, TDZ was reported to have induced higher somatic embryogenesis in protocalli than even 2,4-D (Lehminger-Mertens & Jacobsen, 1989).…”
Section: Discussionmentioning
confidence: 94%
“…Low concentrations of TDZ were effective in inducing multiple in vitro shoots in peanuts cultures (Joshi et al, 2008). In Lens culinaris Medik., 0.5 µM TDZ also stimulate in vitro shoots formation (Chhabra et al, 2008). However, in response to 2.5 µM TDZ, they noticed complete inhibition in the shoots proliferation.…”
Section: Cultured In Vitromentioning
confidence: 94%
“…Auxins have long been reported to be the main inducers of somatic embryogenesis (Sharp et al 1980;Maheswaran and Williams 1984), however, in some cases, cytokinins, such as BAP (Laxmi et al 1999;Pacheco et al 2007) and TDZ (Visser et al 1992;Gill et al 1993;Chhabra et al 2008), also support this morphogenetic event. Nevertheless, our results provide evidence that the association of NAA/TDZ is required for the acquisition of competence of the subepidermal parenchymatous tissue in the adventitious buds that induct somatic embryogenesis via dedifferentiation and transdifferentiation.…”
Section: Unicellular Somatic Embryogenesis and Secondary Organogenesismentioning
confidence: 99%